O processo de securitização e despolitização do imigrante: a política migratória italiana nos anos 1990-2000 - Alves, Lais Azeredo [UNESP] (2015)
This master thesis deals with the securitization of immigration process, taking as a study case the migration policy of Italy. The objective is to discuss and demystify the immigrant construction processes as an irregular, a criminal and especially as a threat to the State in its social, cultural, political and economic areas. In this sense, in the first chapter we discuss the theoretical construction of these practices and their predominantly political character. The categorization as a threat influences the formulation of violent actions against immigrants, who may even violate some rights. However, the use of draconian securitarian practices become increasingly commonplace. In the second chapter, we analyze how the securitization of immigration occurred essentially in the European framework- what is essential to understand what happened in Italy- and how the regionalization process was crucial in differentiating the irregular immigrant as the Other and then in its categorization as a threat, at the same level of transnational crimes such as terrorism. In the third chapter, we analyze the case of Italy, whose changes in migration policy symbolically reflect the processes of criminalization and securitization of the immigrant as an institutionalized and legalized political practice. Finally, it is concluded that the process of securitization of immigration is part of a political act and not technical and that instead of a hyperpolitization - in the securitarian perspective -, there is a de-politicization of immigrant, since their citizenship is misused in the name of state security.